Wine Tourism and Wine Marketing in Family-Owned Micro Wineries in Guadalupe Valley, Mexico / Enoturismo e Comercialização de Vinho em Micro Vinícolas de Propriedade Familiar no Vale de Guadalupe, México - García Fernández, Adrian; Meraz Ruiz, Lino; Díaz Gómez, Eduardo Raúl (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2018)
Abstract Given the importance of the wine sector in Baja California, Mexico, the purpose of this research is to explore the tourism and marketing characteristics of family-owned micro wineries with a production of no more than 5,000 annual/boxes of wine from the Guadalupe Valley, and to identify the socio-demographic consumption parameters. Based on the results, recommendations were made with the cautionary note that more research is needed to address the gap of information that exists in this topic. The research design was a mixed one, qualitative and quantitative, in which a convenience sample of 200 visitors to the Guadalupe Valley were surveyed, and 17 experts in the domain area were interviewed, which allowed to gather data about wine shopping behavior, wine marketing, wine tourism and country background. The results indicated the existence of a significant relationship between dependent and independent variables using Chi Square analysis in SPSS (type of wine + frequency of consumption, type of retailer and willingness to pay). Additionally, a large number of smaller, family-owned wineries, that have limited production runs, and diversify their services via restaurant and boutique type lodging, was uncovered. Conclusions are drawn and implications discussed. Keywords Wine Tourism. Marketing. Small Family Wineries. Baja California, Mexico. RESUMO Dada a importância do setor vitivinícola em Baja California, no México, o objetivo desta pesquisa é o de apresentar as características turísticas e mercadológicas das micro vinícolas de propriedade familiar no Vale de Guadalupe, que produzem anualmente mais de 5.000 caixas de vinho, e de identificar os parâmetros sociodemográfico de consumo. Com base nos resultados, foram feitas recomendações, mas com a advertência de que mais pesquisas são necessárias para abordar a lacuna de informações sobre a questão. O delineamento da pesquisa foi misto, qualitativo e quantitativo, envolvendo uma amostra, por conveniência, de 200 visitantes do Vale no Guadalupe. Foram entrevistados 17 especialistas, o que permitiu coletar dados sobre o comportamento de compra de vinho, marketing de vinhos e enoturismo. Os resultados indicaram a existência de uma relação significativa entre variáveis dependentes e independentes, utilizando a análise de Qui-Quadrado no SPSS (tipo de vinho + frequência de consumo, tipo de varejista e disposição de pagar). Além disso, constatou-se a existência de um grande número de vinícolas menores, de propriedade familiar, com produção limitada e diversidade de serviços, como restaurantes e hotéis boutique. PALAVRAS-CHAVE Enoturismo. Marketing. Micro Vinícolas Familiares. Baixa California, Mexico. AUTORES Adrián Garcia Fernández – Mestre. Profesor de la Universidad Autónoma de Baja California, Ensenada, Baja California, Mexico. Orcid: https://orcid.org/0000-0003-1476-9796 E-mail: adrian.garcia.fernandez@uabc.edu.mx Lino Meraz Ruiz – Doutor. Profesor de Universidad Autónoma de Baja California, Ensenada, Baja California, Mexico. Orcid: https://orcid.org/0000-0002-7724-9176 E-mail lino.meraz@uabc.edu.mx Eduardo Raúl Díaz Gómez – Doutor. Doutor. Profesor de Centro de Enseñanza Técnica y Superior - CETYS Universidad, Tijuana, Baja California, Mexico. Orcid: https://orcid.org/0000-0003-0053-8751 E-mail: eduardo.diaz@cetys.mx REFERENCES Aaker, D., Day, G., & Kumar, V. (2001). Investigación de mercados. Mexico: Editorial Limusa. Ahmed, S. (1986). Understanding residents’ reaction to tourism marketing strategies. Journal of Travel Research, 25(2), 13-18. Link Alpizar, V. A. & Maldonado, M. M. (2009). Integración de la Ruta del Vino en Querétaro, un producto innovador. Quivera, 11(2), 97-109. Link Armstrong, G., & Kotler, P. (2003). Fundamentos de Marketing. Mexico: Pearson Education. Barber, N., Dodd, T. & Ghiselli, R. (2008). Capturing the Younger Wine Consumer. Journal of Wine Research, 19(2), 123-141. Link Barco, E. (2014). Factores determinantes del funcionamiento económico del sector vitivinícola en la Denominación de Origen Calificada Rioja (DOCa Rioja) y su adaptación a los cambios en el entorno económico. Tese de doutorado. Logroño: Universidad de La Rioja. Link Bautzer, D. (2010). Marketing de cidades: construção de identidade, imagem e futuro. Sao Paulo: Atlas S. A. Bennet, P. & Harrel, G. (1975). The Role of Confidence in Understanding and Predicting Buyers’ Attitudes and Purchase Intentions. Journal of Consumer Research, 2(2), 110-117. Link Berselli, C. & da Silva, E. (2017). Turismo e Marketing: Parque Turístico Nossa Senhora da Conceição, em Canguçu, RS, Brasil. Revista Rosa dos Ventos – Turismo e Hospitalidade, 9(1), 49-63. Link Briedenhann, J. & Wickens, E. (2003). Tourism Routes as a Tool for the Economic Development of rural Areas-Vibrant hope or impossible Dream? Journal Tourism Management, 25(1), 71-79. Link Bringas, N. L. & Israel J. I. (2004). El turismo alternativo: una opción para el desarrollo local en dos comunidades indígenas de Baja California. Economía, Sociedad y Territorio, 4(15), 551-590. Link Bruwer, J. (2003). South Africa Wine Routes: Some Perspectives on the Wine Tourism Industry’s Structural Dimensions and Wine Tourism Product. Tourism Management, 24(1), 423-435. Link Buil, I., Martínez, E. & Montaner, T. (2012). La influencia de las acciones de marketing con causa en la actitud hacia la marca. Cuadernos de Economía y Dirección de la Empresa, 15(2), 84-93. Link Camacho, A. (2016). Análisis de las estrategias de adaptación a la escasez hídrica de las empresas vitivinícolas del Valle de Guadalupe, B. C. Tese de doutorado. Tijuana: El Colegio de la Frontera Norte. Link Camussi, G. M. & Zamora, J. I. (2016). Turismo enológico en Uruguay: ¿qué quiere el visitante local? PASOS – Revista de Turismo y Patrimonio Cultural, 14(4), 963-980. Link Castillo, A. M., Núñez, J. M. & Sánchez, S. M. (2016). Local Community’ Perceptions on Tourist Impacts and Associated Development: A Case Study on Sal and Boa Vista Islands. Mediterranean Journal of Social Sciences, 7(1), 383-394. Link Celaya, D. (2014). El desarrollo del sector vitivinícola en Baja California (2000-2013): Un análisis desde la perspectiva del desarrollo endógeno. Tese de doutorado. Tijuana: El Colegio de la Frontera Norte. Link Chang, P. L. & Chieng, M. H. (2006). Building Consumer-Brand Relationship: A Cross-Cultural Experiential View. Psychology & Marketing, 23(11), 927-959. Link Charters, S. & Ali-Knight, J. (2002). Who is the wine tourist? Tourism Management, 23(3), 311-319. Link Clemente-Ricolfe, J. S., Escribá-Pérez, C., Rodríguez-Barrio, J. E. & Buitrago-Vera, J. M. (2012). The potential wine tourist market: the case of Valencia (Spain). Journal of Wine Research, 23(2), 185-202. Link Das, G. (2014). Factors affecting Indian shoppersx³ attitude and purchase intentions: An empirical check. Journal of Retailing and Consumer Services, 21(4), 561-569. Link Diamantopoulos, A., Schlegelmilch, B. & Palihawadana, D. (2011). The relationship between country-of-origin image and brand image as drivers of purchase intentions: A test of alternative perspectives. International Marketing Review, 28(5), 508-524. Link Durán, A., Álvarez, J. & del Río, M. (2017). Bases de datos internacionales, la cobertura de la producción científica sobre turismo gastronómico. p. 52-70. In: Norrild, J. A. (Org.). Gastronomía y Turismo, Destinos con sal y pimienta. España: Centro de Investigaciones y Estudios Turísticos (CIET). Fernández, G. & Guzmán, A. (2003). El patrimonio industrial como recurso para organizar rutas turísticas. Actas del III Encuentro de Turismo Cultural Naya. Buenos Aires, Argentina. Link Festa, G., Cuomo, M. T., Metallo, G. & Festa, A. (2016). The (r)evolution of wine marketing mix: From the 4Ps to the 4Es. Journal of Business Research, 69(5), 1550-1555. Link Ghvanidze, S., Velikova, N., Dodd, T. H. & Oldewage-Theron, W. (2016). Consumers’ environmental and ethical consciousness and the use of the related food products information: The role of perceived consumer effectiveness. Appetite, 107(1), 311-322. Link Getz, D. (2000). Explore wine tourism, management, development and destinations. New York: Cognizant Communications Corporation. Getz, D. & Brown, G. (2006). Critical Success Factors for wine tourism regions: A demand analysis. Tourism Management, 27(1), 146-158. Link Google Maps (s.f.). Location of the Guadalupe Valley. Link Gómez, M., González-Díaz, B. & Molina, A. (2015). Priority maps at wine tourism destinations: An empirical approach in five Spanish wine regions. Journal of Destination Marketing & Management, 4(4), 258-267. Link González, S. & Fuentes, N. A. (2013). Matriz de insumo-producto vitivinícola de Baja California, México. Revista de Economía, 30(81), 57-88. Link Hall, C. M. & Mitchell, R. (2001). Wine Tourism in Mediterranean: A tool for restructuring and development. Thunderbird International Business Review, 42(4), 445-465. Link Hall, C. M., Sharples, L., Cambourne, B. & Mancionis, N. (2000). Wine Tourism around the world: development, management and markets. London: Elsevier. Hamari, J. (2015). Why do people buy virtual goods? Attitude toward virtual good purchases versus game enjoyment. International Journal of Information Management, 35(1), 299-308. Link Hollebeek, L. D., Jaeger, S. R., Roderick, J. B. & Balemi, A. (2007). The influence of involvement on purchase intention for new world wine. Food Quality and Preference, 18(8), 1033-1049. Link Horn, C. & Simmons, D. (2002). Community adaptation to tourism: comparisons between Rotorua and Kaikoura, New Zeland. Tourism Management, 23(2), 133-143. Link Ilicic, J. & Webster, C. (2011). Effects of multiple endorsements and consumer-celebrity attachment on attitude and purchase intentions. Australasian Marketing Journal, 19(4), 230-237. Link Instituto Español de Comercio Exterior (2012). El mercado de vino en México. Madrid: Oficina Económica y Comercial de la Embajada de España en México. Jurincic, I. & Bojnec, S. (2010). Wine tourism development: the case of the wine district in Slovenia. Tourism: An International Interdisciplinary Journal, 57(4), 435-448. Kolyesnikova, N., Dodd, T. H. & Duhan, D. F. (2008). Consumer attitudes towards local wines in an emerging region: a segmentation approach. International Journal of Wine Business Research, 20(4), 321-334. Link Korça, P. (1998). Resident perceptions of tourism in a resort town. Leisure Sciences: An Interdisciplinary Journal, 20(3), 193-212. Link Laroche, M., Kim, C. & Zhou, L. (1996). Brand familiarity and confidence as determinants of purchase intention: An empirical test in a multiple brand context. Journal of Business Research, 37(2), 115-120. Link Lockshin, L., Corsi, A. M., Cohen, J., Lee, R. & Williamson, P. (2017). West versus East: Measuring the development of Chinese wine preferences. Food Quality and Preference, 56(2), 256-265. Link López-Guzmán, T. J., Rodríguez, J. & Viera, A. (2013). Revisión de la literatura científica sobre enoturismo en España. Cuadernos de Turismo, (32), 323-326. Link López-Guzmán, T. J. & Sánchez, S. M. (2008). La creación de productos turísticos utilizando rutas enológicas. PASOS - Revista de Turismo y Patrimonio Cultural, 6(2), 159-171. Link López-Moreno, I. & Thomé, H. (2015). Los pueblos mágicos como enclaves territoriales: el caso de Tequisquiapan y la Ruta del Queso y el Vino de Querétaro, (p. 303-325). In: Pablos, J. (Org.). Pueblos Mágicos: discursos y realidades. Una mirada desde las políticas públicas y la gobernanza Ciudad de México: Repositorio Institucional de la Universidad Autónoma del Estado de México. Lu, L. C., Chang, W. P. & Chang, H. H. (2014). Consumer attitudes toward bloggers’s sponsored recommendations and purchase intention: The effect of sponsorship type, product type, and brand awareness. Computer in Human Behavior, 34(1), 258-266. Link Malhotra, N. K. (2006). Pesquisa de marketing: uma orientação aplicada. Porto Alegre: Bookman. Mazodier, M. & Merunka, D. (2014). Beyond brand attitude: Individual drivers of purchase for symbolic cobranded products. Journal of Business Research, 67(1), 1552-1558. Link McCole, P., Ramsey, E. & Williams, J. (2010). Trust considerations on attitudes towards online purchasing: The moderating effect of privacy and security concerns. Journal of Business Research, 63(9-10), 1018-1024. Link McGehee, N. G. & Andereck, K. L. (2004). Factors predicting rural residents’ support of tourism. Journal of Travel Research, 43(2), 131-140. Link Meraz, L. & Ruiz, A. V. (2016). El enoturismo de Baja California, México: un análisis de su oferta y comparación con la región vitivinícola de La Rioja, España. Revista Investigaciones Turísticas, (12), 73-98. Link Millán, G. & Melián, A. (2008). Rutas turísticas enológicas y desarrollo rural. El caso estudio de la Denominación de Origen Montilla-Moriles en la provincia de Córdoba. Papeles de Geografía, (47-48), 159-170. Link Mueller, S. & Lockshin, L. (2008). How important is wine packaging for consumers? On the reliability of measuring attribute importance with direct verbal versus indirect visual methods. Annuals of 4th International Conference of the Academy of Wine Business Research, Siena. Link Orozco, A. (1999). Investigación de Mercados: Concepto y Práctica. Bogotá: Editorial Norma S. A. Orta, M., Olague, J. T., Lobo, M. O. & Cruz, I. (2016). Importancia y valoración de los componentes de satisfacción de la experiencia enológica en Valle de Guadalupe, Baja California: contribuciones al proceso de gestión sustentable. Revista de Análisis Turístico, 22(2), 39-55. Link Pedragosa, V., Biscaia, R. & Correia, A. (2015). The role of emotions on consumers’ satisfaction within the fitness context. Motriz: Revista de Educação Física, Rio Claro, 21(2), 116-124. Link Pelegrín-Borondo, J., Arias-Oliva, M. & Olarte-Pascual, C. (2016). Emotions, Price and quality expectations in hotel services. Journal of Vacation Marketing, 23(4), 322-338. Link Perdue, R., Long, P. T. & Allen, L. (1990). Resident support for tourism development. Annals of Tourism Research, 17(4), 586-599. Link Quiñónez, J. J., Bringas, N. L. & Barrios, C. (2012). La Ruta del Vino de Baja California. Patrimonio Cultural y Turismo Cuadernos, (18), 131-149. Link Rodríguez, J., López-Guzmán, T., Cañizarez, S. M. & Jiménez, M. (2010). Turismo del vino en el Marco de Jeréz. Un análisis desde la perspectiva de la oferta. Cuadernos de Turismo, (26), 217-234. Link Ruiz, A. V. & Gil, C. R. (2012). Caso 8 Bodega Puelles: Sinergia entre el marketing mix de la bodega y el enoturismo (p. 355-368). In: Escuela Superior de Gestión Comercial y Marketing (Org.). Marketing del vino España: Ediciones Pirámide. Ruiz, W. (2014). Elementos para un diagnóstico de la vitivinicultura en México. Revista de Economía, 31(83), 9-50. Link Saavedra, M. L. & Hernández, Y. (2008). Caracterización e importancia de las MIPYMES en Latinoamérica: Un estudio comparativo. Actualidad Contable Faces, 11(17), 122-134. Link Sánchez, L. (2007). Localización territorial y organización productiva de la industria vinícola del Valle de Guadalupe. Aproximación a la incidencia de la industria vinícola en el desarrollo económico del Valle de Guadalupe (México) y La Manchuela (España). Tese de doutorado. La Mancha: Universidad de Castilla. Secretaría de Desarrollo Económico (2004). Plan Estratégico del Cluster Vitivinícola. Mexicali: Gobierno del Estado de Baja California. Secretaría de Estado de Turismo (2000). Propuesta para la asistencia técnica para el desarrollo del estudio de definición del producto “Rutas del Vino de España”. Servicio de Publicaciones del Ministerio de Industria, Comercio y Turismo. Madrid, España. Secretaría de Turismo (2015). Bulletin 161: Sector Turismo, el mayor generador de empleos: Enrique de la Madrid. Distrito Federal: Secretaría de Turismo del Gobierno Federal. Secretaría de Turismo del Estado de Baja California (2011). Ruta del Vino de Baja California. Tijuana: Gobierno del Estado de Baja California. Secretaría de Turismo del Estado de Baja California (2014). Las fiestas de la vendimia y el turismo enológico en Baja California (Bulletin). Tijuana: Observatorio Turístico de Baja California. Szmulewicz, P. (2007). Métodos de evaluación del potencial turístico de viñas y valles vinícolas. Ponencia 1er. Congreso Internacional de Turismo enológico, Jerez, Spain. Tang, V. C. M., Tchetchik, A. & Cohen, E. (2015). Perceptions of wine labels by Hong Kong Chinese consumers. Wine Economics and Policy, 4(1), 12-21. Link Teng, L. (2009). A comparison of two types of price discounts in shifting consumers’ attitudes and purchase intentions. Journal of Business Research, 62(1), 14-21. Link Thomé, H. (2016). Aprovechamiento recreativo de los Sial: el consumidor implícito del turismo agroalimentario (p. 155-170). In: Renard, M. C. (Org.). Mercados y desarrollo local sustentable. Ciudad de México: Red de Sistemas Agroalimentarios Localizados (Red Sial-México). Thomé, H., Vizcarra, I. & Espinoza, A. (2015). Performancia y fractalización como herramienta de metabolización de los espacios rurales. El caso de la Ruta del Queso y el Vino de Querétaro. Spanish Journal of Rural Development, 6(1), 29-44. Link Tomljenovic, R. & Faulkner, B. (2000). Tourism and older residents in a sunbelt resort. Annals of Tourism Research, 27(1), 93-114. Link Trejo-Pech, C. O., López-Reyna, C., House, L. A. & Sarmiento-Pérez, F. J. (2010). Globalization in the Wine Industry and the case of Baja California Mexico. Annals of 20th Annual World Food and Agribusiness Forum and Symposium 2010, Boston, USA. Link Truong, V. D. & Hall, C. H. (2016). Corporate social marketing in tourism: To sleep or not to sleep with the enemy? Journal of Sustainable Tourism, 25(7), 884-902. Link Velásquez, G. A. (2007). Diseño de un modelo de sistema enoturístico para la región vitivinícola del estado de Querétaro. Dissertação de Mestrado. México, Distrito Federal: Instituto Politécnico Nacional. Vieira, A., López-Guzmán, T. & Rodríguez, J. (2013). Análisis del enoturista en la Denominación de Origen del Jeréz-Xerés-Sherry (España). Tourism & Management Studies, 9(2), 37-43. Link Villanueva, E. C. (2015). The Anglo-Saxon New World Wine Producers’ Paradigms Shift in Wine Business. Global Business & Economics Anthology, Business & Economics Society International, Worcester. Wang, X., Yu, C. & Wei, Y. (2012). Social media peer communication and impacts on purchase intentions: A consumer socialization framework. Journal of Interactive Marketing, 26(1), 198-208. Link Williamson, P. O., Lockshin, L., Leigh, I. & Mueller, S. (2016). Influencing consumer choice: Short and medium term effect of country of origin information on wine choice. Food Quality and Preference, 51(1), 89-99. Link Xu, S., Barbieri, C., Anderson, D. & Leung, Y. (2016). Residents perceptions of wine tourism development. Tourism Management, 55(1), 276-286. Link Zamora, J. & Barril, M. E. (2007). Turismo y vino. Un estudio formativo sobre la evolución de las rutas del vino en Chile. Estudios y Perspectivas en Turismo, 16(2), 173-191. Link PROCESSO EDITORIAL Recebido: 11 NOV 2017. Avaliado: NOV-DEZ 2017. Aceito: 21 MAI 2018